Real Time Nitrogen Management Through Leaf Colour Chart and Chlorophyll Meter in Wheat (Triticum Aestivum L.) Of Jammu (Bangladesh Journal of Botany, 2023)
A field experiment was conducted to assess the effect of real time nitrogen management through leaf colour chart and chlorophyll meter in wheat. The experimental results revealed that Leaf color chart ≤5 based nitrogen application recorded significantly higher growth, yield and yield attributes, which was statistically at par with leaf color chart ≤ 4, sufficiency index and leaf color chart ≤3. However, recommended nitrogen application recorded significantly highest agro physiological efficiency. Sufficiency index recorded highest benefit cost ratio (B:C) which was followed by leaf color chart ≤ 4 and leaf color chart ≤ 5.Bangladesh J. Bot. 52(2): 277-282, 2023 (June)